The Effect of Chest Physiotherapy on Oxygen Saturation and Respiratory Rate in Pediatric Pneumonia - Luthfianto, Muhammad Najib; Irdawati, Irdawati (Sekolah Tinggi Ilmu Kesehatan Kendal, 2023)
Pneumonia is a disease that infects the respiratory tract. The main complaints that often occur in pneumonia patients are shortness of breath, increased body temperature, and coughing. Apart from being a medical parameter for certain diseases, out of a total of six parameters used for the National Early Warning Score (NEWS), oxygen saturation and respiratory rate are two parameters to assess patient's condition. The purpose of the study was to explore the impact of chest physiotherapy and evaluate changes in oxygen saturation and respiratory rate in pediatric pneumonia patients. The research method in this application is application of interventions using case studies. The informative sampling method used was the purposive sampling technique. This research was conducted on July 10, 2023. This type of research is quantitative using a comparative method, where researchers will compare the results before and after the chest physiotherapy intervention. The inclusion criteria of this study are data on children aged 3–4 years. The types of data collection are interviews, actions, and documentation. The instrument used by researchers is pulse oximetry. Conclusion: There is difference in results before and after being given chest physiotherapy in children with pneumonia.